2020
DOI: 10.1093/advances/nmaa063
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effects of Dietary Interventions on Disease Progression and Symptoms of Adults with Multiple Sclerosis: An Umbrella Review

Abstract: Multiple sclerosis (MS) is a chronic inflammatory autoimmune disease of the central nervous system. The role of diet in the progression of MS and severity of symptoms remains unclear. Various systematic literature reviews (SRs) have reported the effects of single nutrients on MS progression or the role of dietary factors on specific symptoms of MS. Narrative reviews have examined the effects of various dietary patterns in MS populations. An umbrella review was undertaken to collate the findings from review art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 97 publications
3
19
0
Order By: Relevance
“…However, Bagur et al reported in their systematic review that existing studies on the effect of vitamin D supplementation in MS are inconsistent with respect to EDSS, MRI lesions, overall functional status, and relapse rate [ 13 ]. It has been suggested that empirical replacement with high doses of vitamin D supplementation (at least 4000 IU/day orally) and for a prolonged period appears to be safe and is associated with low risk for adverse events, although available data are limited [ 12 , 19 , 20 , 21 ].…”
Section: Mechanisms Of Ms Pathology—the Effect Of Diet/nutritional Fa...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, Bagur et al reported in their systematic review that existing studies on the effect of vitamin D supplementation in MS are inconsistent with respect to EDSS, MRI lesions, overall functional status, and relapse rate [ 13 ]. It has been suggested that empirical replacement with high doses of vitamin D supplementation (at least 4000 IU/day orally) and for a prolonged period appears to be safe and is associated with low risk for adverse events, although available data are limited [ 12 , 19 , 20 , 21 ].…”
Section: Mechanisms Of Ms Pathology—the Effect Of Diet/nutritional Fa...mentioning
confidence: 99%
“…Conversely, one Swedish and one Australian study reported low incidence of MS in people following diets enriched in PUFAs [ 5 , 12 , 13 , 25 , 26 ]. Results from meta-analyses suggest that PUFAs may reduce the frequency of relapses, but are not effective against the progression of the disease [ 1 , 19 ]. In human studies, a low fat diet supplemented with PUFAs was associated with lower levels of disability assessed by EDSS, slight improvement in relapse rat, as well as improved quality of life [ 13 , 25 ].…”
Section: Mechanisms Of Ms Pathology—the Effect Of Diet/nutritional Fa...mentioning
confidence: 99%
“…MS is a chronic inflammatory autoimmune disease of the central nervous system 25 . Learning and memory dysfunction has been shown to be a common symptom in MS patients and is associated with hippocampal neuron demyelination, but the exact mechanism remains opaque 2,13 .…”
Section: Discussionmentioning
confidence: 99%
“…There is a lack of strong and consistent evidence for dietary interventions in people with MS, demonstrating any effect on key outcomes of MS progression. More robust studies focusing on foods rather than nutrients are needed to strengthen the evidence [ 67 ]. At present, it is necessary to provide objective information to the patient, taking into account the growing importance of some interest points in the origin and maintenance of the disease, such as nutrition as a possible cofactor influencing the inflammatory cascade, gastrointestinal symptoms, the state of the microbiota and intestinal barrier, allergies and individual food intolerances or obesity in MS patients.…”
Section: Introductionmentioning
confidence: 99%